2017
DOI: 10.1038/s41598-017-00228-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of nicosulfuron under acidic environment caused by oxalate secretion of a novel Penicillium oxalicum strain YC-WM1

Abstract: A novel Penicillium oxalicum strain YC-WM1, isolated from activated sludge, was found to be capable of completely degrading 100 mg/L of nicosulfuron within six days when incubated in GSM at 33 °C. Nicosulfuron degradation rates were affected by GSM initial pH, nicosulfuron initial concentration, glucose initial concentration, and carbon source. After inoculation, the medium pH was decreased from 7.0 to 4.5 within one day and remained at around 3.5 during the next few days, in which nicosulfuron degraded quickl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…All other reagents used were of analytical grade. The microbial community was enriched using modified mineral salt medium (MSM) modified with glucose (1.0 g/L) and supplemented with 20 µL trace element solution 25 . LB (Difco), tryptic soy agar medium (TSA, Difco), and tryptic soy broth (TSB, Difco) were used to isolate degradative strains.…”
Section: Methodsmentioning
confidence: 99%
“…All other reagents used were of analytical grade. The microbial community was enriched using modified mineral salt medium (MSM) modified with glucose (1.0 g/L) and supplemented with 20 µL trace element solution 25 . LB (Difco), tryptic soy agar medium (TSA, Difco), and tryptic soy broth (TSB, Difco) were used to isolate degradative strains.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical hydrolysis of the sulfonylurea linkage has been described as the main abiotic degradation process (Sarmah and Sabadie, 2002), its rate being greater as pH of the medium decreases (Berger and Wolfe, 1996). This phenomenon was also observed for Penicillium oxalicum YC-WM1 where nicosulfuron degradation was due to medium acidification resulting from oxalate secretion by the fungal strain (Feng et al, 2017). Two degradation products are usually formed: 2-amino-4,6-dimethoxypyrimidine (ADMP) and 2-(aminosulfonyl)- N,N -dimethyl-3-pyridinecarboxamide (ASDM), the latter being able to cyclize at basic pH (Sarmah and Sabadie, 2002).…”
Section: Introductionmentioning
confidence: 59%
“…Our results showed that P. cucumerina AR1 can also be used to reduce nicosulfuron contamination since we demonstrated that (i) it was tolerant to nicosulfuron in contrast to what was described for other fungal species (Karpouzas et al, 2014) and (ii) it was able to degrade the nicosulfuron herbicide both in planktonic (Figure 2) and in biofilm conditions with various simple and complex carbon sources (glucose, leaf or wood; Figure 7). Regarding the literature, this is the first time that a leaf-associated fungal strain able to degrade nicosulfuron has been isolated in freshwater, the other ones being isolated from agricultural soil or sludge (Yang et al, 2008; Zhang et al, 2011, 2012; Lu et al, 2012; Song et al, 2013; Zhao et al, 2015a,b, 2018; Wang et al, 2016; Carles et al, 2017a; Feng et al, 2017; Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations